2008
DOI: 10.1182/blood-2008-02-140533
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 1 mediates the rapid anti-inflammatory effects of neutrophil-derived microparticles

Abstract: Polymorphonuclear leukocyte (PMN)–derived microparticles display inhibitory properties on target cells as assessed in vitro; since PMNs contain abundant amounts of the endogenous anti-inflammatory protein annexin 1 (AnxA1), we tested here whether biologically active AnxA1 could be present in PMN-derived microparticles. PMN adhesion to human umbilical vein endothelial cell (HUVEC) monolayers led to the generation of microparticles that contained AnxA1, as detected by Western blotting, flow cytometry, and mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
244
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(261 citation statements)
references
References 39 publications
(69 reference statements)
13
244
0
4
Order By: Relevance
“…Although a number of mechanistic details about the regulation of granulocyte migration by GCs are still unknown, a large body of data indicates that Anxa1 plays a role in this function (27,(41)(42)(43). Previously published results have demonstrated that Anxa1-KO mice show a high degree of neutrophil recruitment in a zymosan model of peritonitis, which supports its important role in migration (44).…”
Section: Discussionmentioning
confidence: 85%
“…Although a number of mechanistic details about the regulation of granulocyte migration by GCs are still unknown, a large body of data indicates that Anxa1 plays a role in this function (27,(41)(42)(43). Previously published results have demonstrated that Anxa1-KO mice show a high degree of neutrophil recruitment in a zymosan model of peritonitis, which supports its important role in migration (44).…”
Section: Discussionmentioning
confidence: 85%
“…Dorsal s.c. air pouches were prepared as described in Dalli et al (23). PBS (PBS+0.01% DMSO), AnxA1 2-50 (0.5 to 500 ng/ mouse), or CR-AnxA1 2-50 (0.5 to 500 pg/mouse) were administered i.v.…”
Section: Murine Air Pouchmentioning
confidence: 99%
“…Human peripheral blood PMNs and HUVECs were isolated as in Dalli et al (23). The HUVECs were plated in 35-mm dish until confluent and then incubated with human recombinant TNF-a (10 ng/ml, 4 h; R&D Systems).…”
Section: In Vitro Flow Chambermentioning
confidence: 99%
“…Plasmatic levels of LMVs have been associated with unstable plaques in asymptomatic patients with high-grade carotid stenosis [13] or with progression of diabetic retinopathy [14]. LMVs are ambivalent bioactive structures affecting both proinflammatory [15,16] and anti-inflammatory processes [17]. LMVs have been primarily ascribed procoagulant properties because of the tissue factor (TF) exposure [18,19] together with procoagulant phospholipids such as phosphatidylserine (PS).…”
Section: Introductionmentioning
confidence: 99%